Estudio del comportamiento del cuerpo y aletas plegables de un cohete, para un sistema de lanza cohetes múltiple - Pimentel Villasmil, Pablo Emilio (2014)
En este trabajo se presentan resultados de los estudios de simulación aerodinámica y análisis de vibraciones del cuerpo de un nuevo diseño de cohete y sus aletas plegables, para experimentar que es posible diseñar y construir un dispositivo como este, capaz de realizar en vuelo horizontal y comportamiento aerodinámico estable, además de mantener su trayectoria balística, diseñado como un posible elemento balístico de un dispositivo tipo lanza cohetes múltiple, con la utilización de material y tecnología nacional, y a bajo costo. La aerodinámica de un cohete es importante en su manufactura, y está definida principalmente por el diseño de partes como la nariz ,la forma del fuselaje y las aletas estabilizadoras. La aerodinámica se puede ver afectada negativamente por vibraciones aeroelásticas y como resultado, este trabajo pretende estudiar el comportamiento vibratorio del nuevo cohete. Para esto, se realizaron diversas pruebas modales en condiciones de laboratorio, tanto estáticas como dinámicas, y análisis por computadora. Esta será la primera parte, para un posible diseño posterior, de un sistema de lanza cohetes múltiples a ser instalado en una aeronave. Se presenta un nuevo diseño de las aletas deben tener la capacidad de estar plegadas o abatidas, y al momento del disparo y su salida del tubo deberán extenderse a su posición de vuelo, siendo su función principal proporcionar la fuerza de rotación requerida para mantener la trayectoria balística. El objetivo del trabajo es la realización del diseño y análisis aerodinámico y comportamiento en vuelo haciendo un diseño CAD (Computer Aided Design) y luego una simulación CFD (Dinámica Computacional de Fluidos), más concentrado en las aletas del cohete, y luego una verificación de vibraciones y análisis Modal a fin de determinar su comportamiento en vuelo, modos propios de vibración y trayectoria balística. ABSTRACT Purpose and Method of Study Mexico has a very interesting and some aerospace unknown past. There are national studies where attempts have been made in the field of rocketry and rocket engines and manufacture thereof. Studies of aerodynamic simulation and vibration analysis of designing a new rocket body and fins were performed folding, to experience it is possible to design and build a device like this, capable of level flight and stable aerodynamic performance, in addition to maintain its ballistic trajectory, ballistics designed as a possible element of a multiple launch rocket type device, using domestic materials and technology, and low cost. Variety of simulated and physical tests, both static and dynamic, using various fixtures and computer analysis were made. This is the first part, for a subsequent design of a multiple launch rocket system to be installed on an aircraft. The aerodynamics of a rocket is important in manufacturing, the nose of the rocket is essential as well as the shape of the fuselage and stabilizer fins. The big difference in this project to other designs rockets gliding, is based on the rocket to the subject of this thesis are several, even more so considering that you must have typical ballistic considerations of a rocket attack air to air or air-ground, particularly rotating on its axis, to achieve and maintain a fixed hit the selected target path. A big consideration for this, is that unlike the vertical free flight rocket, is the movement of center of gravity (CG), as its displacement is kept perpendicular to the surface of the ground, and maintains the same path aircraft. In this case, we must be very precise considerations for moving the CG, since a substantial change could cause loss of sense of stability and parallel to the axis of the rocket trajectory with respect to its own flight path, with very bad consequences. On the other hand fins for stability control of this design are unique and specific for the same, as for the concept design, the rocket must exit tube, so the fins must be able to be folded or folded down, and when shooting and pipe outlet should be opened to their flight position. These fins provide more stability to the flight of the rocket, its primary function is to provide the rotational force required to maintain ballistic trajectory. The aim of this work is the realization of the design and aerodynamic analysis and flight behavior by a CAD design and then a CFD (Computational Fluid Dynamics) simulation, more concentrated on the fins of the rocket, and then verify Modal vibration analysis determine their flight behavior, modes of vibration and ballistic trajectory. Contributions and Conclusions After reviewed various bibliographies, internet references and background, became an early form conceptual design and fabrication of a prototype for the static tests. This project serves as input to the possible development of aerospace research, or rather a continuation of what was started sometime so energetically, and motivate future professionals explore further the field of astronautics and rocketry in the country, because now the field of science and engineering has not generated the necessary interest. To put into practice a project of this category, you need not only large economic investments is to use the equipment and systems already available in our research. For this reason and with the results, it is found that it was a very useful and rewarding to practice the skills of engineering students exercise, and thereby contribute to national development.